PENDAMPINGAN LEMBAGA PAUD DALAM MEMAHAMI 8 STANDAR NASIONAL PENDIDIKAN GUNA PERCEPATAN AKREDITASI - Herlida, Annisa (Madani: Jurnal Pengabdian Ilmiah, 2022)
This study aims to provide assistance and understanding of 1) the eight national education standards that form the basis of accreditation instruments, 2) Each instrument item in each PAUD accreditation standard, and 3) Supporting documents that need to be prepared for accreditation submission. In achieving the objectives, several activities were carried out, namely 1) Providing an understanding of the eight national standards that form the basis of accreditation instruments, 2) Providing an understanding of each instrument item in each accreditation standard, 3) Assistance to institutions when preparing supporting documents. The assistance activities were carried out at Mutiara Hati Play Group, Fanesya Play Group and AL-Anshor Kindergarten in Kalianda, South Lampung. The result of this development activity is the institution's understanding of the eight national education standards and the institution's understanding of the items of PAUD accreditation instruments to prepare documents supporting the accreditation submission.